Judges’ Opinion in Accepting Divorce Cases with Time Limits (Study of Judges of Balikpapan, Banjarmasin, and Pelaihari Religious Court) - Rahmawati; Diana Rahmi (Interdisciplinary Explorations in Research Journal, 2023)
Abstract This research aims to find out the opinions of Balikpapan, Banjarmasin, and Pelaihari Religious Court Judges regarding considerations for accepting divorce cases with a time limit and the reasons underlying these opinions. This type of research is empirical legal research. The data extracted in this research are the opinions and reasons of the Balikpapan, Banjarmasin, and Pelaihari Religious Court Judges regarding divorce with a time limit. The data sources or informants for this research were nine judges. This research is empirical legal research with a sociological approach. Data was collected using interview techniques. After collecting the data, it is processed by editing and matriculation. The data was then analyzed using qualitative descriptive methods. The research results show that the judge stated that divorce with a time limit is a rule that can be negotiated in severe divorce cases. Thus, the judge must make ijtihad with other laws. This is based on Article 50 of Law No. 48 of 2009 and the rules of fiqh, namely, the judge's decision can eliminate differences. Three judges thought that the 6-month time limit for reasons of continuous disputes and quarrels or separation of residence is cumulative, where both reasons must reach the minimum time if they are to be submitted to the court. Six other judges thought that the six-month time limit was an alternative. This is required for reasons of separation of residence. All Judges relied on Supreme Court Circular Letter Number 1 of 2022. Some others added Article 19 of Government Regulation Number 9 of 1975 and Article 116 of Presidential Instruction Number 1 of 1991 on the Compilation of Islamic Law. Keywords: Divorce, Time Limits, Judge's Considerations Abstrak Penelitian ini bertujuan untuk mengetahui pendapat Hakim Pengadilan Agama Balikpapan, Banjarmasin, dan Pelaihari tentang pertimbangan menerima perkara perceraian dengan batas waktu serta alasan yang mendasari pendapat tersebut. Jenis penelitian ini ialah penelitian hukum empiris. Data yang digali pada penelitian ini adalah pendapat dan alasan Hakim Pengadilan Agama Balikpapan, Banjarmasin, dan Pelaihari mengenai perceraian dengan batas waktu. Sumber data atau informan penelitian ini adalah sembilan orang Hakim. Penelitian ini merupakan penelitian hukum empiris dengan pendekatan sosiologis. Data dikumpulkan dengan teknik wawancara. Setelah terkumpul data diolah dengan editing dan matrikasi. Data kemudian dianalisis dengan menggunakan teknik deskriptif kualitatif. Hasil penelitian menunjukkan Hakim menyatakan perceraian dengan batas waktu adalah peraturan yang bisa dinegosiasikan pada perkara perceraian yang berat. Dengan demikian Hakim harus berijtihad dengan hukum lain. Hal ini dilandasi oleh Pasal 50 UU No. 48 Tahun 2009 dan kaidah fiqih yaitu keputusan Hakim dapat menghilangkan perbedaan. Tiga orang Hakim berpendapat batas waktu 6 bulan pada alasan perselisihan dan pertengkaran terus-menerus atau berpisah tempat tinggal bersifat kumulatif, yang dimana kedua alasan tersebut haruslah mencapai waktu minimal tersebut jika ingin diajukan ke Pengadilan. Enam orang Hakim lainnya berpendapat bahwa batas waktu 6 bulan ini bersifat alternatif. Yaitu diharuskan pada alasan berpisah tempat tinggal. Semua Hakim bersandar pada Surat Edaran Mahkamh Agung Nomor 1 Tahun 2022 dan sebagian lain menambahkan Pasal 19 Peraturan Pemerintah Nomor 9 tahun 1975 dan Pasal 116 Instruksi Presiden Nomor 1 Tahun 1991 Kompilasi Hukum Islam. Kata Kunci: Perceraian, Batas Waktu, Pertimbangan Hakim.